2009
DOI: 10.2140/jomms.2009.4.941
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear bending response of giant magnetostrictive laminated actuators in magnetic fields

Abstract: We report numerical and experimental investigations into the nonlinear bending behavior of magnetostrictive laminated actuators under magnetic fields. Magnetostrictive actuators were fabricated from thin layers of Terfenol-D and metal, and the magnetostriction of the devices was measured. A nonlinear finite element analysis was employed to evaluate the contribution of magnetic domain switching to the second-order magnetoelastic constants in the Terfenol-D layer. The effect of a magnetic field on the nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…It has also been found that Terfenol-D exhibits the fracture load reduction as the loading rate decreases. A similar behavior has been observed for other materials, such as TiAl alloys [19] and piezoelectric ceramics [20,21]. Since Terfenol-D material properties are loading rate-dependent, here it is assumed that the critical radius R c , which depends on the material, varies with the loading rate.…”
Section: N O T a T I O N Asupporting
confidence: 55%
“…It has also been found that Terfenol-D exhibits the fracture load reduction as the loading rate decreases. A similar behavior has been observed for other materials, such as TiAl alloys [19] and piezoelectric ceramics [20,21]. Since Terfenol-D material properties are loading rate-dependent, here it is assumed that the critical radius R c , which depends on the material, varies with the loading rate.…”
Section: N O T a T I O N Asupporting
confidence: 55%
“…Making use of magnetic field dependent material properties, the model calculated the nonlinear behavior. The finite element computations were provided by modifying the program with routines developed by our previous work (9), (10) .…”
Section: Journal Of Solid Mechanics and Materials Engineeringmentioning
confidence: 99%
“…[3] They are typically used in automotive industry, as opening regulators in injection control valves, in avionics, as sensors and actuators in vibrations' control, and in robotics, as micropositioning actuators. Although the strain property of magnetostrictive materials under a magnetic field (Joule effect) is usually exploited, these materials have also the dual ability to change their magnetic properties as a consequence of a deformation (Villari effect).…”
Section: Introductionmentioning
confidence: 99%